Vitamin D Deficiency Impacts Exposure and Response of Pravastatin in Male Rats by Altering Hepatic OATPs - Peng, Jinfu; Yang, Guoping; Huang, Zhijun (Frontiers in Pharmacology, 2022)
This study aimed to determine the effect of vitamin D (VD) deficiency on the efficacy and pharmacokinetics of pravastatin and clarify whether the effects are mediated by Organic anion-transporting polypeptides (OATPs). Experiments were conducted in rats to explore the effect of VD deficiency on the pharmacodynamics and pharmacokinetics of pravastatin. In the pharmacodynamic study, rats were fed a VD-free or VD-supplement high-fat diet for 25-30 days, and plasma 25(OH)VD was dynamically monitored. The response of pravastatin (changes in blood lipids) on rats were then examined after 15 days of pravastatin treatment. In the pharmacokinetic study, rats were fed a VD-free or VD-supplement diet for 25-30 days. The pharmacokinetics of single oral dose pravastatin was then studied, and intestinal and hepatic Oatp1a1 and Oatp2b1 expression was determined using quantitative polymerase chain reaction (qPCR) and western blot. Furthermore, OATP1B1 and OATP2B1 expression in Huh7 cells with or without 1,25(OH)2D were assessed via qPCR and western blot. For the pharmacodynamic study, the decrease of total cholesterol and increase of high-density lipoprotein cholesterol in VD-deficient rats were smaller than in VD-sufficient rats, indicating that VD deficiency reduced the response of pravastatin in rats. For the pharmacokinetic study, the plasma exposure slightly increased, and liver exposure decreased in VD-deficient rats, but not significantly. VD deficiency decreased the Oatp1a1 and Oatp2b1 expression in the liver, but not in the small intestine. Similarly, OATP1B1 and OATP2B1 protein levels in Huh7 cells were reduced when 1,25(OH)2D was absent. In conclusion, VD deficiency can decrease the response of pravastatin in rats by reducing the liver pravastatin exposure and expression of hepatic OATPs, consistent with the extended hepatic clearance model theory.